2016
DOI: 10.1103/physreve.93.062208
|View full text |Cite
|
Sign up to set email alerts
|

Covariant Lyapunov vectors of chaotic Rayleigh-Bénard convection

Abstract: We explore numerically the high-dimensional spatiotemporal chaos of Rayleigh-Bénard convection using covariant Lyapunov vectors. We integrate the three-dimensional and time-dependent Boussinesq equations for a convection layer in a shallow square box geometry with an aspect ratio of 16 for very long times and for a range of Rayleigh numbers. We simultaneously integrate many copies of the tangent space equations in order to compute the covariant Lyapunov vectors. The dynamics explored has fractal dimensions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 42 publications
4
32
0
Order By: Relevance
“…Further, the spectrum of dissipative LV was found to be localized in Fourier space. Other work with the Rayleigh-Bénard convection showed that the energy spectra of the CLV were not independent of the Lyapunov indices [36]. Given the present result, it can be expected that the first few CLV also have a non- localized energy spectrum.…”
Section: Localization Of Chaotic Responsesupporting
confidence: 40%
See 1 more Smart Citation
“…Further, the spectrum of dissipative LV was found to be localized in Fourier space. Other work with the Rayleigh-Bénard convection showed that the energy spectra of the CLV were not independent of the Lyapunov indices [36]. Given the present result, it can be expected that the first few CLV also have a non- localized energy spectrum.…”
Section: Localization Of Chaotic Responsesupporting
confidence: 40%
“…It has been reported [36,60] in different chaotic systems that only a small part of the physical space was responsible for most of the perturbation growth in chaotic systems. This property is called the localization.…”
Section: Localization Of Chaotic Responsementioning
confidence: 99%
“…However, many chaotic fluid systems are not uniform hyperbolic. For a Kolmogorov flow simulated with 224 DOFs (Inubushi et al 2012) and for a 3D Boussinesq equations simulated with 5 × 10 5 DOFs (Xu & Paul 2016), researchers found for both cases that the angles between CLVs can be very small. Currently, there are not many results regarding hyperbolicity for CFD simulated 3D Navier-Stokes fluid systems.…”
Section: Introductionmentioning
confidence: 99%
“…CLVs have since attracted a large amount of scientific interest and proved to be a fruitful source of insight, especially into phase-space structures of highdimensional dynamical systems. In particular, CLVs have been used to study e. g. dynamics of rigid disk systems [32,33], chaotic motion in spatially extended systems [34,35], stability properties of geophysical models [36] and collective chaos in systems of coupled oscillators [8,9,37].…”
Section: A Lyapunov Analysismentioning
confidence: 99%